Dialysis Requiring Acute Kidney Injury in Acute Cerebrovascular Accident Hospitalizations. Issue 11 (November 2015) - Nadkarni, Girish N.; Patel, Achint A.; Konstantinidis, Ioannis; Mahajan, Abhimanyu; Agarwal, Shiv Kumar; Kamat, Sunil; Annapureddy, Narender; Benjo, Alexandre; Thakar, Charuhas V.
Abstract : Background and Purpose—: The epidemiology of dialysis requiring acute kidney injury (AKI-D) in acute ischemic stroke (AIS) and intracerebral hemorrhage (ICH) admissions is poorly understood with previous studies being from a single center or year. Methods—: We used the Nationwide Inpatient Sample to evaluate the yearly incidence trends of AKI-D in hospitalizations with AIS and ICH from 2002 to 2011. We also evaluated the trend of impact of AKI-D on in-hospital mortality and adverse discharge using adjusted odds ratios (aOR) after adjusting for demographics and comorbidity indices. Results—: We extracted a total of 3 937 928 and 696 754 hospitalizations with AIS and ICH, respectively. AKI-D occurred in 1.5 and 3.5 per 1000 in AIS and ICH admissions, respectively. Incidence of admissions complicated by AKI-D doubled from 0.9/1000 to 1.7/1000 in AIS and from 2.1/1000 to 4.3/1000 in ICH admissions. In AIS admissions, AKI-D was associated with 30% higher odds of mortality (aOR, 1.30; 95% confidence interval, 1.12–1.48; P <0.001) and 18% higher odds of adverse discharge (aOR, 1.18; 95% confidence interval, 1.02–1.37; P <0.001). Similarly, in ICH admissions, AKI-D was associated with twice the odds of mortality (aOR, 1.95; 95% confidence interval, 1.61–2.36; P <0.01) and 74% higher odds of adverse discharge (aOR, 1.74; 95% confidence interval, 1.34–2.24; P <0.01). Attributable risk percent of mortality was high with AKI-D (98%–99%) and did not change significantly over the study period. Conclusions—: Incidence of AKI-D complicating hospitalizations with cerebrovascular accident continues to grow and is associated with increased mortality and adverse discharge. This highlights the need for early diagnosis, better risk stratification, and preparedness for need for complex long-term care in this vulnerable population.